The possibility of applying the DECAM methodology to enhance the quality of digital human resources performance (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to develop work practices and administrative decision-making processes by adopting the DACUM methodology as a foundational approach for transitioning toward modern training programs and their practical applications in the workplace. Such programs require digital knowledge skills and high-performance competencies to achieve a qualitative shift in professional practices and to scientifically optimize the utilization of resources. This, in turn, contributes to improving the distribution of tasks and duties in alignment with actual organizational needs and emerging global changes.To identify the research problem, the researcher relied on personal interviews as a preliminary exploratory tool, based on a set of pre-prepared questions answered by a purposive sample of (10) officials representing different administrative levels. The findings revealed several key issues, most notably the lack of awareness within the Baghdad Al-Rusafa Health Directorate regarding modern training concepts that correspond to real needs and contemporary global developments, particularly the DACUM methodology. In addition, the directorate suffers from the absence of an integrated digital system capable of enhancing digital performance, which hinders progress toward effective digital transformation in its operations.The applied aspect of the study was based on personal interviews and a workshop involving (13) employees, aimed at identifying strengths, weaknesses, and proposed improvements. Furthermore, the practical analysis was reinforced through a questionnaire employing a five-point Likert scale, administered to a sample of (165) employees with diverse responsibilities and specializations. The questionnaire consisted of (40) items, and the data were analyzed using a set of descriptive and inferential statistical methods to examine relationships and effects.The study reached several conclusions, the most significant of which is the existence of a statistically significant correlation and effect of the DACUM methodology in enhancing the quality of digital performance of human resources.
Keywords: DACUM Methodology; Human Resources Digital Performance